IMPACT OF FUNDING IN INSURTECH ON PREMIUM PERFORMANCE OF INSURANCE BUSINESS - Yadav, Durgesh; Ram Milan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
New technologies such as Blockchain, Internet of Things, Chatbots, Telematics, and Artificial Intelligence are driving innovation in the insurance industry. Insurance innovation has a substantial impact on economic and industry success. This paper explores the effects of InsurTech on the logicality of insurance sector and presents many perspectives on the topic. Examining the benefits that accrue for the insurer and the consumer, this article tries to explain the basics and significance of new technology in the insurance market. Hypotheses are used to check the performance of certain factors related to insurance. Secondary sources were used to collect data. The overall performance of InsurTech has been analyzed with the help of IBM SPSS Statistics Software. Regression analysis as it presents a comprehensive analysis of how InsurTech innovations contribute to better risk management, more accurate underwriting, and enhanced customer engagement. Through case studies and empirical data, the research highlights the positive correlation between InsurTech adoption and premium growth, demonstrating that technological advancements not only drive competitive edge but also give greater profitability and ability to sustain in the insurance sector. The findings underscore the transformative potential of InsurTech in reshaping traditional insurance practices and fixing new standards for industry performance.